P1386Continuous, transcutaneous carbon-dioxide monitoring in complex electrophysiological procedures in conscious sedation - is there a safer way to sleep?. (18th June 2020) - Weinmann, K; Lenz, A; Heudorfer, R; Aktolga, D; Pott, A; Rattka, M; Rottbauer, W; Dahme, T
Abstract: Funding Acknowledgements: Karolina Weinmann was supported by the Hertha-Nathorff fellowship from Ulm University Background – Ablation of cardiac arrhythmias by complex electrophysiological procedures is a growing field. A moderate to deep sedation is needed to immobilize the patient to warrant a safe and effective intervention. The administrated medication to obtain an adequate sedation has respiratory depressant side effects and could cause respiratory complications, like hypercapnia and hypoxia. Purpose – Our aim was to investigate the feasibility and accuracy of an additional, continuous transcutaneous carbon-dioxide (tpCO2) measurement during moderate to deep sedation in complex electrophysiological catheter ablations. Methods – Consecutive patients received an electrophysiological intervention with need for deep sedation. Routine hemodynamic monitoring was performed by the measurement of non-invasive blood-pressure, oxygen saturation and half-hourly venous blood gas analysis. Additionally, patients received a tpCO2 sensor on the forehead with an automated, continuous documentation of transcutaneous oxygen saturation and carbon-dioxide. A precise sedation protocol was performed and administrated drugs were registered. Results – We included 110 patients to the analysis. Fifty patients received cryoballoon pulmonary vein isolation, 58 patients 3D-mapping procedure and two patients ventricular tachycardia ablation. The mean procedure time was 135.1 ± 63.5 minutes and the fluoroscopy time was 21.5 ± 10.9 minutes. To achieve an adequate sedation a mean of 5.0 ± 0.8 mg midazolam, 583.8 ± 320.4 mg propofol, 72.0 ± 30.3 µg fentanyl and 0.2 ± 0.1 mg remifentanil were administrated. Hypercapnia (pCO2 > 70 mmHg) was detected in five patient by the tpCO2 monitoring and only in two patients using venous carbon-dioxide partial pressure (vpCO2) analysis. Correlation of tpCO2 and vpCO2 were analyzed half-hourly by Pearsons' correlation coefficient. There was a good correlation during the investigated 120 minutes of procedure time (baseline: r = 0.65, p < 0.0001; 30 minutes: r = 0.75, p < 0.0001; 60 minutes: r = 0.77, p < 0.0001; 90 minutes: r = 0.78, p < 0.0001; 120 minutes: r = 0.85, p < 0.0001). The detected difference between tpCO2 and vpCO2 was at baseline <5 mmHg in 65% (79/110) and <10 mmHg in 96% (103/110), after 30 minutes the difference was <5 mmHg in 71% (78/110) and <10 mmHg in 96% (105/110), after 60 minutes the difference was <5 mmHg in 77% (60/78) and <10 mmHg in 96% (75/78) and after 90 minutes the difference between the two methods was <5 mmHg in 63% (30/48) and <10 mmHg in 98% (47/48) of the cohort. Conclusion – The continuous tpCO2 monitoring is a feasible and precise method with a good correlation to the venous blood gas carbon-dioxide analysis of the standard monitoring during complex catheter ablations in deep sedation. Randomized trials are required to further analyze if tpCO2 monitoring adds further safety to electrophysiological procedures in deep sedation.